Pengaruh Penerapan Model Problem Based Learning Terhadap Peningkatan Pemahaman Konsep Vektor di Jenjang SMA - Suciawaty, Siti Hindun; Lusiyana, Desy; Makhmud, Tohir (STAIN Bengkalis, 2025)
This classroom action research used a mixed-methods approach to analyze the influence of the Problem Based Learning (PBL) model on the vector concept understanding of class XI students. The quantitative analysis showed that the implementation of PBL resulted in an increase in the average student understanding score from the pre-test to the post-test in each research cycle. A significant increase in learning outcomes was observed in Cycle 2, where the average score increased from 63.70 to 81.50. However, the effectiveness of PBL decreased in Cycle 3, reflected in the Normalized Gain (N-Gain) value returning to a low level (0.27) and a smaller increase in the learning success rate compared to the previous cycle (an increase from 30% to 55%). Overall, the PBL model proved effective in improving students' conceptual understanding of vectors, the ability to apply concepts in problem-solving, and students' mathematical communication skills. However, the research findings also identified that the PBL model was less effective in improving students' understanding and skills in drawing vectors, indicating the need for adjustments in learning strategies for this specific aspect.